Generic fixture design algorithms for minimal modular fixture toolkits - Wallack, A.S. (Proceedings of IEEE International Conference on Robotics and Automation, 1996)
Fixturing, i.e. the process of immobilizing a workpiece for manufacturing or assembly operations, is a fundamental task in manufacturing. Fixtures can either be fabricated from scratch or assembled from a toolkit of modular components; the latter approach is termed modular fixturing. Recently, many researchers have proposed generate and test fixture design algorithms for minimal modular fixture toolkits where minimal fixture toolkits incorporate a single degree of freedom and constrain fixture elements to a finite number of locations. Generate and test strategies have succeeded because minimal fixture toolkits can only fixture generic workpieces in a finite number of ways. In this paper, we present alternative minimal toolkits and two generic fixture design algorithms: a complete enumeration algorithm based upon the generate and test paradigm, and an efficacious heuristic hill climbing algorithm. Our generate and test design algorithm is based upon a duality we observed between fixture design and object recognition from sparse probe data. In particular, we reduce the task of completely enumerating fixtures to the task of constructing complete indexing tables.